City Branding – a detailed study of the phenomenon of city branding and a developed case study for a chosen Portuguese city - Valejo, Rita (2016)
Dissertação de Mestrado em Design e Multimédia apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.